QUALITY EVALUATION OF BRANDS OF PROPRANOLOL HCL TABLETS AVAILABLE ON IRAQI MARKET - ABDUL-HASAN, MAZIN THAMIR; MOHAMMED JAWAD, KRAR KADHIM; NEAMAH Al-SHAIBANI, ABULFADHEL JABER; HASAN AL-GBURI, KARRAR MOHAMMED (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study is to evaluate the quality control of marketed tablets containing propranolol hydrochloride available on the Iraqi market and manufactured by different companies. Methods: Different batches of propranolol hydrochloride 40 mg tablets were assessed using quality control tests. Weight variation, diameter, thickness, friability, disintegration time and dissolution study were carried out in this study. Results: Based on the data obtained in this study, all brands of PPL available on the Iraqi market showed weight variation within the acceptable limit of USP. Marketed products of Becardin and Propranolol lie within the acceptable limit of hardness and Inderal was observed to be slightly higher than the normal upper range of USP. Diameter and thickness for all brands were almost the same, except the diameter of Becardin was slightly higher and friability was zero for all brands. All brands demonstrated a time of disintegration of fewer than 30 min. The tested marketed propranolol products; Inderal, Procard, Becardin and Propranolol showed cumulative drug release of 90.08%, 94.46%, 92.4% and 79.51%, respectively at the end of the first 20 min. This variation in the release profile of marketed tablets of Propranolol HCl might be attributed to the excipients present in the marketed tablets where some of these excipients may behave as a disintegrant and enhance dissolution rate while others may act as dissolution retardants. Conclusion: All marketed tablets of Propranolol HCl employed in this study were produced within the standard criteria of tablet manufacturing. Evaluation of quality control of these selected tablets showed acceptable pharmaceutical properties that lie within the limits of USP.